2007
DOI: 10.4049/jimmunol.179.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Natural DNA Repetitive Extragenic Sequences from Gram-Negative Pathogens Strongly Stimulate TLR9

Abstract: Clinical and epidemiologic studies have suggested a connection between infectious agents and autoimmune diseases (1-3). The innate immune response to microbial DNA could be one of the connections between infectious agents and diseases such as chronic inflammatory intestinal diseases (4) or systemic lupus erythematosus (5-7). Furthermore, bacterial DNA could be playing a key role in severe conditions like Gram-negative septic shock (8), in which a dysregulated innate immune response mediated by TLRs has been co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 34 publications
(37 reference statements)
0
28
0
2
Order By: Relevance
“…To enhance the immunostimulatory activity of PO-ODN, several liposomes were applied as a vehicle for delivery. When PO-ODN was encapsulated in DOTAP, the uptake of PO-ODN and the production of IFN-α were enhanced in hPBMCs (18,19). Previously, we screened a natural immunostimulatory PO-ODN from bacterial chromosomal DNA, but the PO-ODN was much less potent in inducing HLA-DRA and hBD-2 promoter activation in RPMI 8226 cells than in mice (13,14,20).…”
Section: Effect Of Ps-odn Encapsulated In Liposomes On Il-8 Promoter mentioning
confidence: 99%
“…To enhance the immunostimulatory activity of PO-ODN, several liposomes were applied as a vehicle for delivery. When PO-ODN was encapsulated in DOTAP, the uptake of PO-ODN and the production of IFN-α were enhanced in hPBMCs (18,19). Previously, we screened a natural immunostimulatory PO-ODN from bacterial chromosomal DNA, but the PO-ODN was much less potent in inducing HLA-DRA and hBD-2 promoter activation in RPMI 8226 cells than in mice (13,14,20).…”
Section: Effect Of Ps-odn Encapsulated In Liposomes On Il-8 Promoter mentioning
confidence: 99%
“…Плазмида p(СатIII) обогащена АТ-парами (область 1q12 1-й хромосомы человека), которые не содержат ни лигандов, ни супрессоров TLR9, однако в составе вектора pBR322 присутствуют CpG-богатые участки ДНК. В качестве положительного контроля использовали ДНК Е. coli в концентрации 50 нг/мл, которая является известным лигандом, взаимодействующим с рецепторами TLR9 [16].…”
Section: результаты и обсуждениеunclassified
“…PO-ODN activates the innate immune system in mice, but triggers relatively low activity in human cells (2). However, it has been reported that activation of the innate immune response in human cells was induced with liposome-encapsulated PO-ODN (DOTAP and lipofectin) (26,27). In testing whether encapsulated dsCpG-DNA has immunostimulatory activity, we found that IL-8 promoter activation, HLA-DRA expression, and IL-8 expression were significantly enhanced in a CG-sequence-independent manner (Figs.…”
Section: Effects Of Pcr-amplified Dscpg-dna On Il-8 and Hla-dra Gene mentioning
confidence: 99%